Tantalum and molybdenum barriers to prevent carbon diffusion in spark plasma sintered tungsten. (15th April 2021) - Kwak, Nojun; Min, Guensik; Oh, Yeonju; Suh, Dong-Woo; Kim, Hyoung Chan; Kang, Sung-gyu; Han, Heung Nam
Abstract: Carbide reduces the ductility of tungsten and leads to brittle intergranular fractures. These fractures are inevitably formed in tungsten by carbon diffusion owing to graphite mold during spark plasma sintering. Here, we introduce protective foils made up of two different carbide-forming elements, molybdenum and tantalum, to minimize the carbide formation. Cross-sectional elemental mapping shows that the tantalum foil suppresses carbon diffusion into tungsten, while the molybdenum foil is not an effective diffusion barrier. Thermodynamic-kinetic simulations demonstrate that the suppressed carbon diffusion in tantalum is attributed to high solubility and low diffusivity. Furthermore, the thermodynamically stable tantalum carbide prevents further carbon diffusion at the tantalum/tungsten interface. For the opposite reason, carbon diffuses faster not only in the molybdenum, but also at the molybdenum/tungsten interface. This study provides strategies to minimize the carbon diffusion during spark plasma sintering as well as an intuition into developing structural materials for extreme carbonaceous environments. Graphical abstract: Image, graphical abstract